Teplonosné látky otopných soustav - Michalíčková, Iveta (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Tématem diplomové práce jsou teplonosné látky otopných soustav. Práce je rozdělena na tři části. V první části je teoreticky rozebraná problematika teplonosných látek. V druhé části je uvedena výpočtová část projektu. Projekt řeší vytápění bytového domu. Jsou zde navrženy dvě varianty zdroje tepla a úpravny vody. Tyto varianty jsou následně zhodnoceny. V poslední části je řešen experiment, který se zabýval kvalitou vody v otopných soustavách.

Theme of diploma thesis is the heat transfer medium in heating systems. The thesis is departed to three parts. In the first part, there is a theoretical solution of heat transfer mediums. In the second part, there is a calculation solution of the project. Project solves heating of the apartment building. There are two variants of heating source and water treatment. Those variants are compared. The last part is experimental part. Theme of the experiment is quality of heating water in heating systems.
The heat transfer medium in heating systems
Keywords: Diplomová práce; teplonosná látka; voda; pára; nemrznoucí směs; vzduch; bytový dům; desková otopná tělesa; plynový kondenzační kotel; úprava vody; změkčování; demineralizace; kvalita vody; pH; vodivost; tvrdost; obsah soli; obsah pevných rozpuštěných látek; Diploma thesis; heat transfer medium; water; steam; antifreezing mix; air; apartment building; radiators; gas condensing boiler; water treatment; water softening; demineralization; water quality; pH; conductivity; hardness of water; salt content in the water; dissolved solids content in water